Un reportaje fotográfico a los pescadores de ASOPEIN en Honda, Tolima: Tradición y Río (2024)
The article emphasizes the importance of addressing cultural and patrimonial issues in the Honda, Tolima community, proposing effective communication strategies and awareness about the preservation of the river Magdalena as a central element of the region's cultural identity. The author uses a photographic reportage on ASOPEIN fishermen to explore and document their culture, traditions, and heritage. The report highlights the social role of fishermen in preserving resources and territorial rights, as well as the importance of their cultural heritage in many Colombian communities. The report also highlights the importance of communication and the role of the community in understanding and preserving cultural heritage. The report also highlights the significance of storytelling in transmitting social, political, and cultural messages, as well as humanizing stories and connecting emotionally with the audience. The article emphasizes the importance of qualitative research, social interaction, and visual representations in understanding the lives of ASOPEIN fishermen and their connection to the river Magdalena.